THE CORRELATION OF COGNITIVE FUNCTION TO BRAIN GYM IN THE ELDERLY - Rianawati, Sri Budhi; Harahap, Herpan Syafii; Raisa, Neila; Setianto, Catur Ari; Nikmahtustsani, Mulika Ade Fitria; Maliga, Helnida Anggun (MNJ (Malang Neurology Journal), 2024)
Background: A decline in cognitive function is often considered normal in the elderly, but the advanced stages of cognitive decline can decrease the ability to perform functional activities. Brain gym is one of the physical activity therapies that is proven to improve cognitive function. The purpose of this study is to know the effect of brain gym on cognitive function. Objective: This study aims to determine the correlation of cognitive function to brain gym in elderly. Methods: This is a queasy experimental study in 70 respondent with a pre and post-test group design. The subjects were elderly who were examined with Montreal Cognitive Assessment Indonesian (MoCA-Ina) and Visual Reproduction Test (VRT) on the first day and given brain gym 13 times, which was done 2 times in 1 week and re-examined MoCA-Ina and VRT after the intervention. Results: The research results show improvement in the MoCA-Ina and VRT pre and post-examinations after being given intervention. In the MoCA-INA examination, the mean score of the pretest was 23.30 and the mean score of the post-test was 24.50, while in the VRT examination, the mean score of the pretest was 10.08, and the post-test mean score was 10.83. However, there was no significant difference between MoCA-Ina or VRT in pre- and post-interventional brain gym (p>0.05). Conclusion: There is a relationship between cognitive function which is marked by an increase in the results of Moca INA and VRT with brain gym in the elderly at Balearjosari Malang